475 DEVELOPING A VIRTUAL CARE HOME SUPPORT FORUM DURING THE COVID-19 PANDEMIC. (14th June 2021) - Ferrigan, L; Hartley, R; Hadley, E; Steward, L; Ngwenya, S; Harmer, J; Robinson, A; Cosmos, S; Wilkinson, I; Tucker, P; Flores, A; Baker, R
Abstract: Introduction: COVID-19 has had a devastating effect on care homes, increasing both morbidity and mortality of residents and staff. Between 2 March and 12 June 2020, COVID-19 was the main cause of death in male care home residents (33.5%) and second for female (26.6%).1 By 1 May 2020, the death rate from all causes in care homes exceeded that in hospital (6, 409 versus 6, 397).2 Thus, care homes had to rapidly adapt to facilitate safe care of patients and staff. Method: An expert outreach team visited a number of care homes in Surrey and Sussex to explore COVID-19 issues in care homes. Key themes were identified that informed topics for the Virtual Care Home Forum, where a series of virtual teaching, training and peer support sessions were hosted either live or on-demand, accessible for all care home staff. Results: 12 sessions were held with an average attendance of 25 people, predominantly care home managers and community healthcare professionals. Real time qualitative feedback was collected and an electronic survey was completed at the end of the series which showed 100% felt the sessions had improved their understanding of the topic, 100% felt the knowledge and skills obtained from the sessions would be useful in their job, 87.5% agreed the sessions would impact or change their practise and 100% felt more supported during the pandemic. Conclusion: It has been an unprecedented year for the NHS, and the care home sector has suffered significantly. In order to provide the best level of care for patients and support for our community colleagues, we must work collaboratively, including provision of education and training. To ensure equal access for all, maintaining user-safety and compliance with government legislation, virtual webinars proved to be an excellent modality. We plan to continue providing training, teaching and support through this means in the future.